Measuring the Perception of the Internal Integration Impact Between Logistics, Marketing and Production on the Time-Oriented Performance of the Supply Chain: The Mediating Variable Role of Information Technologies - Zafer Sayan; Hatice Çal?p?nar; Erdinç Koç (International Journal of Supply Chain Management, 2021)
In today's conditions, the lack of ability of businesses to compete effectively and independently of other members in the supply chain forces businesses to cooperate with these stakeholders. This indicates the importance of supply chain integration and internal integration as a part of it in the performance evaluation dimension. The aim of this study is to demonstrate the perception of the effect of internal integration between logistics, marketing and production, which perform related activities, on the time-oriented performance of the supply chain through the mediating-variable role of Information Technologies. For this purpose, an empirical study was conducted for medium and large enterprises in the manufacturing sector in the provinces of Istanbul and Ankara, and the theoretical model created was analyzed using the bootstrap method for the analysis of the brokerage effect along with the structural equality model. According to the results of the research, it has been found out that the internal integration between logistics, marketing and production directly affects the perception of the impact of the supply chain on time-oriented performance and positively affects the situation when information technologies are used as a medium. This research has been conducted according to the findings and it is important in terms of providing new areas for researchers in the field of supply chain management and showing the perception of the impact of internal integration on performance for managers.